2021
DOI: 10.3390/agronomy11081634
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis and Selection Criteria in Bambara Groundnut Accessions Based Yield Performance

Abstract: The knowledge of genetic variability and breeding techniques is crucial in crop improvement programs. This information is especially important in underutilized crops such as Bambara groundnut, which have limited breeding systems and genetic diversity information. Hence, this study evaluated the genetic variability and established the relationship between the yield and its components in Bambara groundnut based on seed weight using multivariate analysis. A field trial was conducted in a randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
5
14
0
Order By: Relevance
“…According to the results of this study, there is a significant amount of genetic diversity across Bambara groundnut accessions for the quantitative parameters evaluated. Several earlier researchers namely Khan et al [ 15 ], Khan et al [ 17 ], Khiliqi et al [ 8 ], and Khaliqi [ 37 ] effectively apply a similar statistical approach in their genetic diversity research on Vigna subterranea (L.) that confirm our results in this tropical environment. Aliyu et al [ 38 ] conducted a comprehensive study on Bambara groundnuts using a range of morphological features, which confirmed our research findings.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…According to the results of this study, there is a significant amount of genetic diversity across Bambara groundnut accessions for the quantitative parameters evaluated. Several earlier researchers namely Khan et al [ 15 ], Khan et al [ 17 ], Khiliqi et al [ 8 ], and Khaliqi [ 37 ] effectively apply a similar statistical approach in their genetic diversity research on Vigna subterranea (L.) that confirm our results in this tropical environment. Aliyu et al [ 38 ] conducted a comprehensive study on Bambara groundnuts using a range of morphological features, which confirmed our research findings.…”
Section: Discussionsupporting
confidence: 86%
“…Singh and Choudhary [ 31 ] proposed a measuring scale for categorizing the genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) values as low for 0 to 10%, intermediate for 10 to 20%, and high is ≥20% variance. The genotypic coefficients of variation (GCV) and phenotypic coefficients of variation (PCV) for most of the traits were medium to high, a similar pattern of the result was reported by Khan et al [ 15 ], Khaliqi et al [ 8 ] in Bambara groundnut diversity assessment. Direct selection would be effective using the traits of low RD values due to less influence by environmental factors.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations